"I Want to Feel Like a Full Man": Conceptualizing Gay, Bisexual, and Heterosexual Men's Sexual Difficulties. Issue 6 (24th July 2018) - McDonagh, Lorraine K.; Nielsen, Elly-Jean; McDermott, Daragh T.; Davies, Nathan; Morrison, Todd G.
Abstract : Current understandings of sexual difficulties originate from a model that is based on the study of heterosexual men and women. Most research has focused on sexual difficulties experienced by heterosexual men incapable of engaging in vaginal penetration. To better understand men's perceptions and experiences of sexual difficulties, seven focus groups and 29 individual interviews were conducted with gay ( n  = 22), bisexual ( n  = 5), and heterosexual ( n  = 25) men. In addition, the extent to which difficulties reported by gay and bisexual men differ from heterosexual men was explored. Data were analyzed using thematic analysis applying an inductive approach. Two intercorrelated conceptualizations were identified: penis function (themes: medicalization, masculine identity, psychological consequences, coping mechanisms) and pain (themes: penile pain, pain during receptive anal sex). For the most part, gay, bisexual, and heterosexual men reported similar sexual difficulties; differences were evident regarding alternative masculinity, penis size competition, and pain during receptive anal sex. The results of this study demonstrate the complexity of men's sexual difficulties and the important role of sociocultural, interpersonal, and psychological factors. Limitations and suggested directions for future research are outlined.